The experiences of migrant pharmacists: A phenomenographical study - Michelle Flood; Judith D. Strawbridge; James W. Barlow (Elsevier, 2023)
Objectives: To understand the experiences of migrant pharmacists in Ireland as they applied for recognition of their qualifications and registration with the national accrediting body. Methods: Semi structured interviews were conducted with eight participants recruited using purposive sampling. Interview transcripts were subject to a phenomenographic study using a stepwise, inductive approach. Results: Data analysis led to the development of a number of categories or descriptions of understanding that provided insight into the ways that participants experienced and conceptualised the phenomenon under study. Five categories of description were identified. These are (1) the migrator, (2) the navigator, (3) the student again, and (4) the registrant. For some, an additional category, (5) the mentee, was experienced. Within these categories, variation in participants' experiences was explored. Conclusions: Participants reported a variety of reasons for migration, and upon embarking on the process, applicants were required to take on a variety of roles, with variation within each role dependent on a number of personal and external factors. Applicants faced personal, administrative, experiential and regulatory hurdles prior to registration, all of which should inform the development of future iterations of this and similar processes.